1998
DOI: 10.1074/jbc.273.31.19847
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Protein L27 Participates in both 50 S Subunit Assembly and the Peptidyl Transferase Reaction

Abstract: Protein L27 has been implicated as a constituent of the peptidyl transferase center of the Escherichia coli 50 S ribosomal subunit by a variety of experimental observations. To define better the functional role of this protein, we constructed a strain in which the rpmA gene, which encodes L27, was replaced by a kanamycin resistance marker. The deletion mutant grows five to six times slower than the wild-type parent and is both coldand temperature-sensitive. This phenotype is reversed when L27 is expressed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
60
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 42 publications
13
60
0
Order By: Relevance
“…Thus, incorporation of L16 possibly triggers a significant conformational change and facilitates organization of the architecture of the functional site in the 50 S subunit (48). On the other hand, deletion of rpmA encoding L27 in E. coli results in accumulation of the premature 40 S subunit lacking L16, L20, L21, and L27 and inhibition of the peptidyl transferase activity of 70 S ribosome (49). Incorporation of L16 into the 50 S subunit depends on L25, which additionally interacts with YlqF, as evident from the E. coli 50 S subunit assembly map (50).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, incorporation of L16 possibly triggers a significant conformational change and facilitates organization of the architecture of the functional site in the 50 S subunit (48). On the other hand, deletion of rpmA encoding L27 in E. coli results in accumulation of the premature 40 S subunit lacking L16, L20, L21, and L27 and inhibition of the peptidyl transferase activity of 70 S ribosome (49). Incorporation of L16 into the 50 S subunit depends on L25, which additionally interacts with YlqF, as evident from the E. coli 50 S subunit assembly map (50).…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli strains in which L27 was deleted grew six times slower than the wild type (wt), and ribosomes lacking L27 were found to carry sub-stoichiometric amounts of L16, L21, and L20. The PT activity of ΔL27 ribosomes was slightly reduced, both in the presence of Pmn or native A-site substrate (Phe-tRNA Phe ) (Wower et al 1998). Truncation of the N-terminal tail of L27 revealed that the absence of as few as the first three residues reduces the PT activity to the level of ΔL27 ribosomes (Maguire et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several ribosomal proteins of the small subunit (17)(18)(19)(20) and at least one of the large subunit (21) appear to affect the decoding process. Moreover, some ribosomal proteins appear to influence the peptidyltransferase activity of the ribosome (22)(23)(24).…”
mentioning
confidence: 99%